Comparative Modelling Studies of 400 MHz ST-X Quartz SAW Delay Lines for Potential Gas Sensing Applications - THIRUMAL, Venkatesan; RAJU, Banupriya; GANDHI, Pandiyarajan; PANDYA, Haresh M. (Archives of Acoustics, 2018)
Surface Acoustic Wave (SAW) devices like delay lines, filters, resonators etc., are nowadays extensively used as principal solid state components in many electronic applications and chemical vapour sensors. To bring out the best from these SAW devices, computational design and modelling are resorted too. The present paper proposes the modelling of 400 MHz ST-X Quartz based SAW delay line, by three models namely, Impulse Response Model (IRM), Crossed-field Equivalent Circuit Model (ECM) and Couplingof-Modes (COM) model. MATLAB is employed as a computational tool to model the experimental output of the SAW device. A comparative discussion of the modelled device results is also provided.